Soil variation response is mediated by growth trajectories rather than functional traits in a widespread pioneer Neotropical tree - Levionnois, Sébastien; Tysklind, Niklas; Nicolini, Eric; Ferry, Bruno; Troispoux, Valérie; Le Moguedec, Gilles; Morel, Hélène; Stahl, Clément; Coste, Sabrina; Caron, Henri; Heuret, Patrick (Peer Community Journal)

(untitled)
1. Trait-environment relationships have been described at the community level across tree species. However, whether interspecific trait-environment relationships are consistent at the intraspecific level is yet unknown. Moreover, we do not know how consistent is the response between organ vs. whole-tree level. 2. We examined phenotypic variability for 16 functional leaf (dimensions, nutrient, chlorophyll) and wood traits (density) across two soil types, Ferralitic Soil (FS) vs. White Sands (WS), on two sites for 70 adult trees of Cecropia obtusa Trécul (Urticaceae) in French Guiana. Cecropia is a widespread pioneer Neotropical genus that generally dominates early successional forest stages. To understand how soil types impact resource use through the processes of growth and branching, we examined the architectural development with a retrospective analysis of growth trajectories. We expect soil types to affect both, functional traits in relation to resource acquisition strategy as already described at the interspecific level, and growth strategies due to resource limitations with reduced growth on poor soils. 3. Functional traits were not involved in the soil response, as only two traits -leaf residual water content and K content-showed significant differences across soil types. Soil effects were stronger on growth trajectories, with WS trees having the slowest growth trajectories and less numerous branches across their lifespan. 4. The analysis of growth trajectories based on architectural analysis improved our ability to characterise the response of trees with soil types. The intraspecific variability is higher for growth trajectories than functional traits for  C. obtusa, revealing the complementarity of the architectural approach with the functional approach to gain insights on the way trees manage their resources over their lifetime. Soil-related responses of Cecropia functional traits are not the same as those at the interspecific level, suggesting that the effects of the acting ecological processes are different between the two levels. Apart from soil differences, much variation was found across sites, which calls for further investigation of the factors shaping growth trajectories in tropical forests.